Pegbelfermin for reducing transaminase levels in patients with non-alcoholic steatohepatitis: a dose-response meta-analysis of randomized controlled trials - Lu, Yangguang; Yu, Bohuai; Bu, Yiran; Lou, Jialing; Jin, Yan (Frontiers in Medicine, 2024)
Background: The efficacy of Pegbelfermin (PGBF) in treating non-alcoholic steatohepatitis (NASH) remains controversial. Therefore, we conducted a dose-response meta-analysis to explore the effect and pattern of PGBF at different dosages and treatment durations on transaminase reduction in NASH patients. Methods: We conducted searches on PubMed, Embase, Cochrane Library, Web of Science, and ClinicalTrials.gov, and supplemented the search with gray literature and manual searches. Randomized controlled trials (RCTs) evaluating the efficacy of PGBF in NASH patients were included. Risk of bias was assessed by Cochrane Risk of Bias Tool 2.0. We used random-effects models, generalized least squares regression, constrained maximum likelihood, and restricted cubic splines to explore the dose-response relationship. Egger's linear regression was employed to assess publication bias. The study is registered with PROSPERO, CRD42023448024. Results: Four RCT studies from the period 2018-2023, involving 546 participants, were included. No participants discontinued PGBF treatment due to adverse events. High-dose PGBF treatment significantly reduced transaminase levels in NASH patients compared to the low-dose group (ALT %: MD = 14.94, 95% CI = 2.11 to 27.77; AST %: MD = 9.05, 95% CI = 3.17 to 14.92). Longer treatment duration further decreased transaminase levels (ALT %: MD = 8.81, 95% CI = 4.07 to 13.56; AST %: MD = 6.72, 95% CI = 2.62 to 10.81). Egger's test did not reveal significant publication bias (p > 0.05). Further investigation indicated a ceiling effect of PGBF dosage on transaminase reduction at 30 mg/week, and NASH patients experienced a rebound in transaminase levels after 28 weeks of continuous treatment. Conclusion: There is a positive correlation between PGBF dosage and transaminase reduction within a certain range, showing an overall non-linear dose-response relationship. This finding provides guidance for the clinical application of PGBF. Clinicians should be mindful of the dosage ceiling at 30 mg/week and monitor changes in transaminase levels after 28 weeks for timely adjustments in PGBF dosage.